Biosorption of Methylene Blue by Activated Carbon from Sugarcane Waste (ACSW) - Hendri Iyabu; Wiwin Rewini Kunusa; Ishak Isa; Doly Prima Silaban (The Journal of Pure and Applied Chemistry Research, 2021)
This study was aimed to produce and characterized activated carbon from sugarcane bagassebyphysical and chemicalactivation. Physical activation was performed by carbonation process in temperatures 4500C and 6500C. While chemical activationusedH3PO4 10%, FeCl3 10% and KMnO4 10% as activator. The results showed that total yield (%) 49.8396 - 80.635; pH 4.0-7.9; ash content (g) 0.3338-0.8820; adsorption capacity of iod (%) 93.92-99.20. Morphological structure, functional group and Crystal structure was studied by using SEM analysis, FT-IR and XRD Difragtogram respectively.Adsorption capacity(%) of methylene blue 1.5 ppm and 2.5 ppm using UV-VIS Spectrophotometer produces; for H3PO4activatorat 450℃ = 99.24 and ND;at 600℃ = ND and 99.24. FeCl3 activator at 450℃ = 93.8 and 28.68; At 600℃ = ND and 99.24. KMnO4 activator at 450℃ = 61.24 and 65.12; At 600℃ = 39.4 and 53.79.